NAMPT and NAPRT serum levels predict response to anti-TNF therapy in inflammatory bowel disease - Colombo, Giorgia; Caviglia, Gian Paolo; Ravera, Alberto; Tribocco, Elisa; Frara, Simone; Rosso, Chiara; Travelli, Cristina; Genazzani, Armando A.; Ribaldone, Davide Giuseppe (Frontiers in Medicine, 2023)
Nicotinamide phosphoribosyltransferase (NAMPT) and nicotinic acid phosphoribosyl transferase (NAPRT) are intracellular enzymes as well as extracellular proinflammatory cytokines. Several reports have shown that serum NAMPT is increased in patients with inflammatory disorders, including inflammatory bowel diseases (IBD), while nothing is known regarding circulating NAPRT and the presence of either cytokine in patient stools. In the present study, we conducted a retro-perspective study on 180 patients, of which 111 underwent subsequent biological treatment (adalimumab, vedolizumab and ustekinumab). We analysed eNAMPT and eNAPRT concentrations in serum and faeces of IBD patients, correlating them with response to biologics. We now report that eNAMPT and eNAPRT are significantly increased in both serum and stools of IBD patients. NAMPT and NAPRT levels correlate with disease severity, with high sensitivity C reactive protein and with serum IL-6 levels. Importantly, levels of NAMPT in patients starting treatment with adalimumab correlate with response failure at three months: patients with levels above 4 ng/ml were significantly less likely to obtain benefit. Serum NAMPT as a biomarker of response yields a sensitivity of 91%, a specificity of 100% and a PPV of 97%. The present work strongly suggests that a prospective trial evaluating eNAMPT and eNAPRT levels in relation to response to biologicals in IBD should be initiated.